Pengaruh Kualitas Pelayanan dan Kepercayaan Terhadap Kepuasan Wisatawan Pada Puri Sabina Bed and Breakfast Jimbaran Bali - Sedana, I Gede Agus Putra; Susila, I Made Gede Darma; Rusmiati, Ni Nyoman (Universitas Triatma Mulya, 2024)
When a person compares the quality of a product or service with what they anticipated, they are said to be satisfied as a tourist. The purpose of this study was to determine, partially and simultaneously, the impact of trust (X2) and service quality (X1) on visitor satisfaction Y. Data for this study were collected through interviews, questionnaires, and observations at Puri Sabina Bed & Breakfast in Jimbaran, Bali. Visitors to Puri Sabina Bed & Breakfast Jimbaran, Bali constituted the population, and there were 75 respondents in the survey. Two methods of data analysis were used: Multiple Linear Regression and Descriptive Statistical Analysis. According to the test results, this study shows that, in addition to trust having a positive and significant impact on visitor satisfaction, service quality also has a positive and significant effect on visitor satisfaction. Furthermore, it shows that, in addition to their respective effects, service quality and trust significantly affect visitor satisfaction at the same time.